How the Chinese system of charges and subsidies affects pollution control efforts by China's top industrial polluters - Wang, Hua (Policy research working paper, 1999)
China's unique combination of emissions charges and pollution abatement subsidies has given China's most heavily polluting industrial firms incentive to invest in pollution abatement